Institutional and Strategic Aspects State Policy in the Field of the Russian Federation National Security - Plotnikov, V. A.; Prolubnikov, A. V.; Rukinov, M. V. (Глобальная ядерная безопасность, 2022)
The sphere of ensuring national security is an important object of state policy. When managing this sphere, strategic and tactical levels are distinguished, each of which has its own institutional consolidation. In addition, functional areas of national security, such as nuclear and radiation safety, can be distinguished. The article analyzes the texts of the National Security Strategy of the Russian Federation and the Fundamentals of State Policy in the Field of Nuclear and Radiation Safety of the Russian Federation from the perspective of analyzing the potential of the strategic regulatory impact of these documents. The inconsistency of their texts, the lack of complexity in regulating the institutional framework for the implementation of state policy in the field of national security is noted. It is also shown that there is no correlation between these important documents of strategic management. The study allowed the authors to conclude that strategic documents in the field of ensuring the national security of the Russian Federation require its processing and adjustment.